Teste de desenvolvimento motor grosso - 3 (TGMD-3) com o uso do aplicativo gross motor skills para crianças com Síndrome de Down: validade e confiabilidade - Bridi, Daiane (2022)
Children with Down Syndrome, in addition to motor and intellectual delay, also have language delay and impaired verbal memory, which can make it difficult to understand and select the information received to perform certain tasks or more complex motor skills. Thus, adding pedagogical support tools for both assessment and teaching of skills, creating approaches that adapt to the way these children process and perceive the environment, can favor a more adequate assessment of their motor performance. Objective: To test the validity and reliability of the use of the Gross Motor Skills (GMS) visual support application for the Gross Motor Development Test - 3 (TGMD-3) and to analyze the focus of attention and intrinsic motivation with the use of this support in children with Down Syndrome. Materials and methods: A randomized crossover clinical trial, composed of 24 children aged between 3 and 10 years, of both sexes, 10 with Down Syndrome (DS) and 14 neurotypical (NT), obtained for convenience. Motor performance was evaluated using the TGMD-3 following two different protocols for demonstrating skills: traditional protocol (PT) with demonstration performed by the examiner and application protocol (PApp), using animations from the GMS application. In the first evaluation, the randomization of the groups was performed, where half were evaluated by the PT and the other half with the PApp. During the instruction of each protocol, the children were filmed to analyze the focus of attention. After seven days, the groups were reassessed with the inversion of the protocols. A follow-up was performed after 20 days with one of the randomly defined protocols. At the end of each evaluation, the children answered the Intrinsic Motivation Inventory (IMI) to assess how motivated they were with the activities. Results: Both protocols demonstrated good to excellent levels of internal consistency and excellent levels of intra- and inter-rater and testretest reliability. There was no difference in the comparison of the raw data of the TGMD-3 subscales in both groups, between the two protocols, however, there was a significant difference in favor of the PApp, for the DS group, in the total score of the TGMD-3 (PApp: 17 .40±8.06 and PT: 15.90±7.52). The number of attention deviations was significantly lower in the PApp for NT children (41.93±32.62) compared to PT (57.07±43.24), since the time spent with deviations was lower for both groups in the Papp (DS: 75.80±48.90 and NT: 41.00±30.30) compared to PT (DS: 150.00±65.78 and NT: 67.07±49.79). The time of focus of attention showed no difference between the groups as a function of the protocol. The total time spent on instruction was significantly lower with the use of the PApp, for the DS group (409.30±68.15) compared to the PT (502.10±77.02). Regarding intrinsic motivation, there was no statistical difference in the IMI scores, although the scores were favorable to the PApp in both groups. Conclusion: The use of the GMS application is valid and reliable to be used in the application of the TGMD-3, favoring the channeling of attention and optimizing the time spent on test instruction, with promising effects on intrinsic motivation.